Functional and phylogenetic community assembly linked to changes in species diversity in a long‐term resource manipulation experiment. (2nd August 2013) - Gerhold, Pille; Price, Jodi N.; Püssa, Kersti; Kalamees, Rein; Aher, Kaia; Kaasik, Ants; Pärtel, Meelis; de, Francesco
Abstract Question There are contrasting opinions about how communities assemble along a productivity gradient, particularly in relation to competitive interactions. One view is that functionally similar, and closely related species, are less likely to co‐exist (limiting similarity). Alternatively, competitive exclusion may act on dissimilar species because species bearing traits associated with low competitive ability are excluded (weaker competitor exclusion). We ask if patterns of functional and phylogenetic diversity are related to changes in species diversity in response to fertility manipulations. Location Species‐rich mesophytic grassland in Estonia. Methods The grassland has been manipulated from 2002 to 2011 to increase (fertilizer addition) and decrease productivity (sucrose addition) in small‐scale (50 cm × 50 cm) plots. We linked annual increases and decreases in species diversity to changes in functional and phylogenetic diversity. We used abundance‐weighted mean pair‐wise functional or phylogenetic distance of all possible species pairs. Results We found convergence in four traits (plant height, leaf distribution, lateral spread, type of reproduction) and a decrease in mean functional and phylogenetic diversity, in support of weaker competitor exclusion or habitat filtering. There was less support for limiting similarity, with divergence found for two traits associated with decreasing species diversity (leaf distribution in the sucrose treatment and lateral spread in the fertilizer treatment). Conclusions Our results support the view that competition can lead to the exclusion of weaker competitors, rather than increasing functional and phylogenetic diversity, as expected from the principle of limiting similarity. However, multiple assembly processes, which are generally seen as mutually exclusive, are operating simultaneously, albeit on different traits and at different stages of community assembly.